新型无水胸腔负压引流装置在胸外科术后患者中的应用研究 (Zhongguo Fei Ai Za Zhi, 2020)
BACKGROUND AND OBJECTIVE: After general thoracic surgery, a chest tube is usually placed for closed drainage to expel gas accumulation in the thoracic cavity and fluid accumulation to promote lung re-expansion. It can also be observed whether there is active bleeding after the operation and whether there is a pulmonary leak. The conventional drainage of the chest cavity is connected with a water-sealed drainage bottle, and the patient condition is judged by observing the drainage situation and the fluctuation of the water column, which is a very classic method. However, the water-sealed bottle has the disadvantages of being easy to overturn and inconvenient to carry, which is not conducive to the early activities of patients. Under the concept of accelerated rehabilitation, our center applied a new type of anhydrous thorax negative pressure drainage device and achieved good results. The purpose of this study was to observe the effect of a new type of anhydrous thoracic negative pressure drainage device in patients after thoracic surgery. METHODS: Retrospective analysis of patients who underwent lung surgery in the First Affiliated Hospital of Zhejiang University Medical College from January 2018 to December 2019, patients were divided into two groups. One group of patients used a traditional closed-chest drainage water-sealed bottle as a control group, and the other group used a new type of anhydrous negative-pressure drainage bottle as an experimental group. Patients' gender, age, hypertension, diabetes, smoking history, surgical incisions and surgical methods, and the length of hospital stay and postoperative hospital stay were calculated. RESULTS: There were no statistical differences in age, gender, comorbidities (hypertension, diabetes, smoking history), scope of surgery, and duration of surgery between the two groups of patients, but there were statistical differences in surgical incisions between the two groups of patients (P=0.01). We found that patients using the new waterless negative pressure drainage device were shorter than patients with water negative pressure drainage device in terms of postoperative hospital stay and total hospitalization time, and the difference was statistically significant (P=0.02, P=0.04). CONCLUSION: The new type of anhydrous thoracic negative pressure drainage device has a good effect on the rapid recovery and advancement after thoracic surgery.